Pengawasan Internal Pada Produktifitas Kerja Pegawai - Sulistiawaty, Titin (Universitas Madura, 2018)
Internal control is a form for improving employee performance, that is how the achievement of the task execution. Seen from: the target work, the implementation of internal supervision, comparison with the resulting work product. Related to this achievement the result in implementation of the task has not been in accordance with the planned work targets, it has not had an impact on work productivity, so interesting to investigate. This research belongs to the qualitative category in analysis of internal control theory from Mulyadi (2000: 178). Viewed from: employee discipline, deviation, waste, leakage, employee service. Based on the results of research that has been implemented it can be concluded Internal control affects the productivity of employees in value creation on resource management